2017
DOI: 10.2196/medinform.8092
|View full text |Cite
|
Sign up to set email alerts
|

Patient Portal Use and Experience Among Older Adults: Systematic Review

Abstract: BackgroundThe older adult population (65 years or older) in the United States is growing, and it is important for communities to consider ways to support the aging population. Patient portals and electronic personal health records (ePHRs) are technologies that could better serve populations with the highest health care needs, such as older adults.ObjectiveThe aim of this study was to assess the existing research landscape related to patient portal and ePHR use and experience among older adults and to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
177
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(189 citation statements)
references
References 33 publications
(189 reference statements)
10
177
2
Order By: Relevance
“…14,16 Despite the high read rate, the relatively lower use of the portal for ACP compared with article-based AD completion and in-person ACP discussions highlights the need for further evaluation of how and why older adults choose to engage in ACP, including through the patient portal. 20 Our early work described perspectives of early adopters of the ACP tools. 21 More than one-third of interviewees were age 60 years and older and had varying perspectives on usability of portal-based tools compared with article ADs, however that analysis was not after an outreach process to raise awareness about the ACP tools.…”
Section: Discussionmentioning
confidence: 99%
“…14,16 Despite the high read rate, the relatively lower use of the portal for ACP compared with article-based AD completion and in-person ACP discussions highlights the need for further evaluation of how and why older adults choose to engage in ACP, including through the patient portal. 20 Our early work described perspectives of early adopters of the ACP tools. 21 More than one-third of interviewees were age 60 years and older and had varying perspectives on usability of portal-based tools compared with article ADs, however that analysis was not after an outreach process to raise awareness about the ACP tools.…”
Section: Discussionmentioning
confidence: 99%
“…For example, older adults may experience difficulties when using technologies such as mobile devices or smartphones [39]. However, there has been a growing interest in the design of technologies, including innovative health technology design for older adults, who often manage complex health conditions and multiple chronic illnesses, to provide better and more sufficient supportive care services [40]. Our study findings demonstrated that older participants (>65) were interested and had a positive attitude toward using the ASyMS device, although a few of them mentioned that they prefer to use the ASyMS on a larger device with larger font size.…”
Section: Discussionmentioning
confidence: 99%
“…Of nine reviews assessing factors that affect patients' adoption of ePHRs and patient portals [i.e. 10,19,25,130,[131][132][133][134], the current review is the only one that differentiated between factors affecting the intention to use, subjectively-measured use, and objectively-measured use.…”
Section: Strengthsmentioning
confidence: 99%